Cuerpos de mujer en el mundo laboral bilbaíno bajomedieval y moderno (s. XIV –XVI). - Ana María Rivera Medina (Nuevo mundo - Mundos Nuevos, 2008)
Women’s labor was highly regulated in the ordinances and municipal records, and becomes a useful source to appreciate the level of feminine participation in the urban world of Bilbao in the late Middle Ages and in Early Modern period. In Bilbao cities, women played a key role in the urban economic activities. She worked as viticulturist, winemaker, baker, miller, bartender, hostess, fishmonger, linen cloths merchant, and salesperson. Those who performed these activities have a characteristic in common: they always moved within the thin line that separated the legal and illegal, the honest and the dishonest, the morality and the sin. Some of them, living and working in the streets, would be object of permanent attention on the part of the authorities. Their incorporation to working activities differed widely. In our work we will analyze their performances in relation to the obstacles imposed by the legislation, and how they are observed by the public eye in a town that shifts toward modernity in a time of commercial and industrial expansion.